2020
DOI: 10.1039/d0dt02624g
|View full text |Cite
|
Sign up to set email alerts
|

Antenna triplet DFT calculations to drive the design of luminescent Ln3+complexes

Abstract: Density Functional Theory-based methods have been exploited to look into the structural, vibrational and electronic properties of antenna ligands, all of them crucial points for a reliable design of customized...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 57 publications
2
20
0
Order By: Relevance
“…This implies that the central metal and the ligands are mostly independent, and electronic properties are substantially unaffected upon moving from the isolated fragments to the complex. 2 , 28 , 29 Thus, the smaller size of the free ligand compared to that of the corresponding complex allows the estimation of ligand ZFS parameters through more accurate calculations, and the results can be then transferred to their Gd 3+ complexes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This implies that the central metal and the ligands are mostly independent, and electronic properties are substantially unaffected upon moving from the isolated fragments to the complex. 2 , 28 , 29 Thus, the smaller size of the free ligand compared to that of the corresponding complex allows the estimation of ligand ZFS parameters through more accurate calculations, and the results can be then transferred to their Gd 3+ complexes.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental crystal structures of P1 and 1 – 3 are consistent with the presence of multiple rotamers differing for the relative orientation of the aromatic rings. 2 Triplet geometries needed for ZFS parameters have therefore been optimized for all four possible rotamers, herein labeled A, B, C, and D (see Figure S5 of the Supporting Information ). B and C rotamers may be obtained by flipping either the thienyl moiety (B) or the PAH fragment (C) of the predominant species A. Rotamer D is generated by flipping both the thienyl group and the PAH fragment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the commonly used vertical approach, where T1 and the S0 share the same geometry, gives a larger energy gap, since the calculated T1 state exists in a vibrationally excited state. [39][40][41] Solvation effects were included in the calculations using the solvent model based on density (SMD) method and the previously optimized polarizable continuum model (PCM) radius was used for Tb(III) in all solvation calculations without scaling (α = 1.0). 42 Spin density plots of the optimized T1 state for all of the complexes confirmed that the spin density was located on the antenna arm of the ligand (Figure 3A).…”
Section: Molecular Design and Dftmentioning
confidence: 99%